Triathletes in motion - Evans, Marc 1953-; Cappaert, Jane M. (Human Kinetics, 2014)
Traditionally the focus of triathlon is on volume, intensity and training periodization which consists typically of doing particular workouts during the months, weeks and days leading up to a race. But what if triathletes could improve performance without logging extra distance on the road or in the water? This book shows you how